Mediterranean diet affects the metabolic outcome of metabolic dysfunction-associated fatty liver disease - Xiao, Yuji; Zhang, Xue; Yi, Dongxin; Qiu, Fangyi; Wu, Lei; Tang, Yiyong; Wang, Ningning (Frontiers in Nutrition, 2023)
The prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD) is on the rise globally. It is currently one of the most prevalent liver diseases and one of the world's important public health problems. At present, there is no consensus on a pharmacological treatment for MAFLD. By contrast, lifestyle interventions based on exercise and a balanced diet are considered to be the cornerstone of MAFLD management. Mediterranean diet (MD) have a large content of polyphenols, polyunsaturated fatty acids, oleic acid, carotenoids and fiber, which carry out antioxidant, anti-inflammatory and antibacterial benefits. It has been considered to reduce the incidence rate of cardiovascular disease and type 2 diabetes. The purpose of this narrative review is therefore to summarize and analyze the evidence for the effect of MD on metabolic outcomes in MAFLD patients.